A checklist of the freshwater ichthyofauna from El Petén and Alta Verapaz, Guatemala, with notes for its conservation and management - Valdez-Moreno, Martha Elena; Pool-Canul, José; Contreras-Balderas, Salvador (Zootaxa, 2005)
Guatemala is characterized by high diversity of its freshwater fishes. Among the most important regions of biodiversity are the Departments of El Petén and Alta Verapaz, located in the northern part of the country south of the Mexican border. Several authors consider the ichthyofauna of this country to be relatively well studied, but the majority of available information is dispersed and sporadic. We present an updated systematic list, comprising all species collected by us, and which includes an exhaustive check of literature records. A total of 55 collecting localities are included in this study. The total species number is 88, distributed in 47 genera, 24 families, and 14 orders. The two departments together include 35.2% of the total estimated number of fish species for the entire country. The Cichlidae and Poeciliidae are the most speciose families. Of the total of 88 species, 11 are primary fishes, 54 are secondary, and 23 peripheral, according to Myers (1938) classification. One endemic species is known from El Petén and 12 from Alta Verapaz. Three species are considered to be exotics: Ctenopharyngodon idella, Carassius auratus, and Oreochromis aureus. Several of our collections confirm the presence of species not reported for more than 30 years (e.g., Bramocharax species), but others require more study (i.e. Heterandria species). Only 18 species from Guatemala are recognized as threatened or endangered by different organizations, but included are some of the more common and widespread species, such as Astyanax aeneus. Several endemics are excluded from such listings, possibly due to lack of knowledge. The actual condition of the Guatemalan populations for the majority of the fish species, including the endemics, is not known.Guatemala presenta una gran diversidad de peces dulceacuícolas y entre las regiones más